Higher Education: Catalysts for the Development of an Entrepreneurial Ecosystem, or … Are We the Weakest Link?. (July 2017) - Wadee, Ahmed A.; Padayachee, Anshu
The promotion of entrepreneurship requires an ecosystem where Higher Education Institutions (HEI) hold a crucial position in collaboration with all stakeholders. Such systems require a high degree of interaction, involving institutions, people and processes that work together with the goal of creating entrepreneurial ventures that are mutually beneficial and self-sustaining. The university setting may be an ideal starting point such that it would serve to recognise potential entre-preneurs within communities and play critical roles in developing and supporting thriving entrepreneurial ecosystems. They may serve as conveners and collaborators for entrepreneurs and support communities to promote the economic development of the region. Such energy derived from university promoted environments in which learning is encouraged and discoveries are made reflects on Higher Educational aims. Obstacles in this role of universities include a lack of provision of the best instructional methods and venues by universities, programmes and curricula that are not conducive to promoting entrepreneurship, a lack of information on entrepreneurial activities in the informal sector and a dearth of appropriate role models within both universities and the business environment. It is therefore apparent that universities are the missing link for the development of a vibrant entrepreneurial ecosystem in South Africa.